Strategi Terbaik Untuk Meningkatkan Keterampilan Literasi Siswa Menggunakan Metode Pembelajaran Scramble - Salwa Cantika Khoriunnisa; Dinie Anggraeni Dewi; Rizky Saeful Hayat (PT. ALHAFI BERKAH INDONESIA, 2023)
This article examines the positive impact of collaboration in managing the relationship between schools and communities at the elementary school level. The research method used is a literature study method, where various relevant literature sources are used as a basis to evaluate best practices in school-community relationship management. This study reveals that effective collaboration between schools and communities can have a significant positive impact on improving the quality of education in elementary schools. The best practices in managing this relationship involve active participation from parents, guardians, the local community, and relevant institutions in efforts to enhance students' learning experiences. The article also highlights several challenges that may arise in managing school-community relationships, such as cultural differences, lack of resources, and mismatched expectations among the parties involved. However, through inclusive approaches, mutual understanding, and shared commitment, these challenges can be overcome. By implementing best practices in managing school-community relationships, it is expected that elementary schools can create a better learning environment, improve student achievement, and prepare them to face future challenges.